Public, Private, and Faith-Inspired Schools in Ghana : A Comparative Assessment - Adoho, Franck (Taylor and Francis, 2014)
There is no doubt that the contribution of private schools, both faith-inspired and secular, is significant in Africa: private schools fill a gap left by insufficient public education and they provide choice to households. Yet detailed evidence on their market share and characteristics is often not available. How large is the market share of private secular and faith-inspired schools (FISs) in Africa in comparison to public schools? Is it correct to assume that while private secular schools are often affordable only for wealthier families, FISs do reach the poor and provide services at low cost to households? Is it also correct to assume that the education provided by private schools, whether faith-inspired or secular, is on average of better quality than that provided by public schools, or at least that the satisfaction of parents with the schooling provided to their children is higher in private schools than in public schools? The purpose of this article is to consider these questions through a case study of Ghana.